Transition-metal-free synthesis of 3-sulfenylated chromones via KIO3-catalyzed radical C(sp2)–H sulfenylation - Guo, Yanhui; Zhong, Shanshan; Wei, Li; Wan, Jie-Ping (Beilstein Journal of Organic Chemistry, 2017)
The reactions between o-hydroxylphenyl-functionalized enaminones and sulfonyl hydrazines providing 3-sulfenylated chromones via domino chromone ring construction and C(sp2)–H bond sulfenylation have been achieved under transition-metal-free conditions by using KIO3 as the only catalyst.
Keywords: C–H sulfenylation; chromones; domino reaction; free-radical; transition-metal-free